Implementation Of Heian Shodan Kata In Beginners Karateka At Dojo Angkasa Lanud Padang - Mettarmizi, Mettarmizi; Sari, Novita; N, Erizal (Yayasan Sekora, 2019)
Based on the results of observations by researchers on training at the Dojo Angkasa Lanud Padang playing the Heian Shodan Kata, the results obtained by beginners when playing the Heian Shodan Kata decreased. This is thought to be related to the lack of ability of the beginner karateka at the Dojo Angkasa Lanud Padang in performing basic movements (kihon ) Heian Shodan Kata. This research aims to reveal the implementation of the Heian Shodan Kata in the Beginner Karateka of Padang Air Force Base. From the results of the study, which amounted to 16 samples of beginner karateka at the Dojo Angkasa Lanud Padang, data results from each of these beginner karateka were obtained. However, at the time of processing the skill data of Heian Shodan Kata, there were several karateka with low skill scores. After tracing it turned out that the one with a low value was the white belt starter karateka. The number of white belt karateka with low value was 3 karateka. So from 16 samples were made 13 samples. The results of the Horses skill test (Dachi) on the Beginner's karateka at the Dojo Angkasa Lanud Padang is with an average of 53.51. The results of the test for Beginner Skills (Uke) on the Beginner's Karateka at the Dojo Angkasa Lanud Padang were with an average (Mean) of 26.08. The result of the Heian Shodan Kata skill test on the Beginner's karateka at the Dojo Angkasa Lanud Padang is an average of 144.